The role of marginalised women in sanitation initiatives: Somali women in northern Kenya. Issue 1 (2nd January 2017) - Thuita, Wambui; Conn, Cath; Wilson, Kaisa
ABSTRACT: Research has shown women from marginalised communities have significant articulated needs for sanitation that are often unmet. Using focus group discussions with displaced Somali women living in rural villages in northern Kenya, this study found that women's central concerns were for personal safety and convenience rather than hygiene; and for alleviation from the pain and discomfort associated with female genital mutilation and reproduction. Based on the findings, the article recommends organisations supporting sanitation initiatives should adopt approaches responsive to women's particular concerns and needs. It makes specific recommendations for implementing an agenda of participation in a context where women are highly marginalised.